LEXICAL ITEMS IN BATAK TOBA LANGUAGE REPRESENTING FAUNA, FLORA, AND SOCIAL ENVIRONMENT: ECOLINGUISTICS STUDY - Mery Silalahi (Haluan Sastra Budaya, 2019)
In the ecolinguistic view, the relationship between human and nature (ecology) produces a variety of languages (linguistics). Language and environment are two things that influence each other. Change in language, both in the lexicon or grammar, cannot be released from changes in the natural and social environment. On the one hand, environmental changes have an impact on change in language, and on the other hand, the community behavior towards their environment influenced by the language they use. Thus, the dynamics of the existence of the lexicon are affected by changes in the environment of a place the language used. The results of this study prove that there is relationship between language and nature. There are 6 lexicons which be explained in this article. Horbou or buffallo and Dekke or fish: goldfish are lexical items representing fauna. Boras Sipir ni Tondi or Rice and Demban or Sirih or betel leaf are lexical items representing flora. And to the lexical items which representing social environment are Ulos or Woven Cloth and Tortor or Traditional Dance. The six lexical items which are representing natural (two for fauna and flora respectively) and social environment (two lexical items) contain cultural terms in Batak Toba language. Because it is a cultural term, then it cannot be separated from the history of Batak people. The cutural terms then will be analyzed and compared to the present life in Indonesian culture in general. It could have similarities or even differences to the present life in Indonesia.